Використання 3d-моделювання під час розроблення рекламних відеоматеріалів - Іпполітова, В. Є. (ХНУРЕ, 2024)
In the article, study of the opportunities of using 3D graphics to create advertising videomaterials has been conducted. Blender was selected as the primary 3D-modeling tool for creating advertising materials. The process of creating advertising materials was described in detail.
Keywords: реклама; розроблення рекламних відеоматеріалів